Analisis Transaksi Penjualan Pada Recovery.u Computer Menggunakan Algoritma Naive Bayes - Almira Dwi Yuliarti; Corrinna Salsabila Amelia; Dewi Ika Sukarno Putri; Chaerur Rozikin (Pusat Riset dan Inovasi Nasional, 2023)
As time passes, the competition in the realm of venture and technologyis quickly increasing, so that business people are competing to expand their business by utilizing existing technology, and also that their business always survives and thrives in the rapid business competition. Sales at Recovery.u Computer are supposed to continue to mount benefit, one of which is by providing products to market demand so that no harm occur. During this time the company often suffers losses because it does not have a system to predict sales. This research has been past perform and attest that the Naïve Bayes Algorithm can be used to predict sales of products and services at Recovery.u Computer. The research data consists of 4 attributes, namely, transaction date, product line, brand, and purchase status obtained from Recovery.u Computer from January 2023 – October 2023. The yield of the estimation that have been it is known that the calculation procces is assisted by WEKA software, by making a possibility table of each variable and an exactness rate of 98,6248% on the test data that has been curried out, and purposeful this can be informed to Recovery.u Computer to do wiser policy in the future.